2023
DOI: 10.3390/foods12183338
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Prebiotic Effects and Antibacterial Activity of Five Leguminous Honeys

Florinda Fratianni,
Beatrice De Giulio,
Antonio d’Acierno
et al.

Abstract: Honey is a natural remedy for various health conditions. It exhibits a prebiotic effect on the gut microbiome, including lactobacilli, essential for maintaining gut health and regulating the im-mune system. In addition, monofloral honey can show peculiar therapeutic properties. We in-vestigated some legumes honey’s prebiotic properties and potential antimicrobial action against different pathogens. We assessed the prebiotic potentiality of honey by evaluating the antioxidant activity, the growth, and the in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…In an attempt to demonstrate the prebiotic effect of five types of legume honey and the probiotic effect on L. rhamnosus and L. paracasei, ref. [29] used astragalus, carob, alfalfa, sainfoin, and indigo honey in their research. They concluded that the polyphenols present in these types of honey show a prebiotic potential on L. rhamnosus and L. paracasei strains with antagonistic action towards the five most dangerous pathogens depending on the type of honey.…”
Section: Impact Of Prebiotics From New Sources On the Growth Of Speci...mentioning
confidence: 99%
“…In an attempt to demonstrate the prebiotic effect of five types of legume honey and the probiotic effect on L. rhamnosus and L. paracasei, ref. [29] used astragalus, carob, alfalfa, sainfoin, and indigo honey in their research. They concluded that the polyphenols present in these types of honey show a prebiotic potential on L. rhamnosus and L. paracasei strains with antagonistic action towards the five most dangerous pathogens depending on the type of honey.…”
Section: Impact Of Prebiotics From New Sources On the Growth Of Speci...mentioning
confidence: 99%
“…Following the method of Fratianni et al [29], an aliquot from each of the three samples of honey was vigorously mixed with Milli-Q water (1:4 w/v), filtered (0.45 µm; Millipore, Milano, Italy), and subjected to the biochemical analyses.…”
Section: Biochemical Analysesmentioning
confidence: 99%
“…Free-radical-scavenging activity was determined in microplates through the diphenyl-1-picrylhydrazyl (DPPH) test (29). Samples (15.15 µL) were mixed with 303 µL of a methanol solution of DPPH (153 mM).…”
Section: Diphenyl-1-picrylhydrazyl (Dpph) Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, our study supports the notion that most Cu and Zn is bound to proteins, likely exceeding 10 kDa in size. Honey has been confirmed to offer various health benefits, including anti-inflammatory properties [81], antioxidative effects [82], antibacterial properties [83], support for gastric and digestive health [84], cancer prevention potential [85], cancer treatment possibilities [86], and benefits for skin care [87]. Additionally, honey contains several other important compounds, such as polyphenols [88], water-soluble vitamins [89], free amino acids [90], and enzymes [91].…”
Section: Multi-element Concentrations In Honey Proteinsmentioning
confidence: 99%